Pengaruh Penyaringan Secara Tradisional Terhadap Kadar Kesadahan Total Pada Air Sumur Gali di Desa Batang Terap Kecamatan Perbaungan Kab. Serdangbedagai - Rosmayani Hasibuan (Pascasarjana Universitas Negeri Medan, 2015)
Abstract. In use the water has specific requirements, both for households and industry. One of the requirements that must be met is the number of water hardness, the numbers associated with the amount of calcium and magnesium. On the use of water for washing and bathing, excess of calcium and magnesium will reduce the effectiveness of the soap/detergent, even for domestic use the element content should be zero, because of the presence of these elements can cause the crust on cooking utensils. The studies conducted in August to October 2013, about the influence of traditional filtering on total hardness levels in Batang Terap village Perbaungan sub-district Serdang Bedagai regency. The goal of this research is to find out the influence of traditional filtering for the well water total hardness levels. Samples taken as many as 10 samples before filtering and 10 samples after filtering from the same 10 house, which the characteristic feature of water containing total hardness is the formation of crust on cookware. Analysis were performed using complexometry method. Results obtained before screening was 158.36 ppm- 283.55 ppm, and after filtration was 134.82 ppm-179.75 ppm. The result of decreased levels of hardness before and after filtering is 8.13%-36.60% Keywords: well water, total hardness, complexometry